Low expression of IL-18 and IL-18 receptor in human skeletal muscle is associated with systemic and intramuscular lipid metabolism—Role of HIV lipodystrophy - Lindegaard, Birgitte (PLoS One, 2018)
INTRODUCTION: Interleukin (IL)-18 is involved in regulation of lipid and glucose metabolism. Mice lacking whole-body IL-18 signalling are prone to develop weight gain and insulin resistance, a phenotype which is associated with impaired fat oxidation and ectopic skeletal muscle lipid deposition. IL-18 mRNA is expressed in human skeletal muscle but a role for IL-18 in muscle has not been identified. Patients with HIV-infection and lipodystrophy (LD) are characterized by lipid and glucose disturbances and increased levels of circulating IL-18. We hypothesized that skeletal muscle IL-18 and IL-18 receptor (R) expression would be altered in patients with HIV-lipodystrophy. DESIGN AND METHODS: Twenty-three HIV-infected patients with LD and 15 age-matched healthy controls were included in a cross-sectional study. Biopsies from the vastus lateralis muscle were obtained and IL-18 and IL-18R mRNA expression were measured by real-time PCR and sphingolipids (ceramides, sphingosine, sphingosine-1-Phosphate, sphinganine) were measured by HPLC. Insulin resistance was assessed by HOMA and the insulin response during an OGTT. RESULTS: Patients with HIV-LD had a 60% and 54% lower level of muscular IL-18 and IL-18R mRNA expression, respectively, compared to age-matched healthy controls. Patients with HIV-LD had a trend towards increased levels of ceramide (18.3±4.7 versus 14.8±3.0,p = 0.06) and sphingosine (0.41±0.13 versus 0.32±0.07, and lower level of sphinganine (p = 0.06). Low levels of muscle IL-18 mRNA correlated to high levels of ceramides (r = -0.31, p = 0.038) and sphingosine-1P (r = -0.29, p = 0.046) in skeletal muscle, whereas such a correlation was not found in healthy controls. Low expression of IL-18 mRNA in skeletal muscle correlated to elevated concentration of circulating triglycerides (R(p) = -0.73, p<0.0001). Neither muscle expression of IL-18 mRNA or ceramide correlated to parameters of insulin resistance. CONCLUSION: IL-18 (mRNA) in skeletal muscle appears to be involved in the regulation of intramuscular lipid metabolism and hypertriglyceridemia.